Competitive intelligence for dummies - Underwood, Jim (Wiley,John Wiley [distributor], 2013)
Competitive intelligence is the art of defining, gathering, analyzing, and distributing intelligence about products, customers, competitors, individuals, concepts, information, ideas, or data needed to support executives and managers in making strategic decisions for an organization. "Competitive Intelligence For Dummies" introduces you to this fascinating subject and gives you the tools you need to incorporate it into your business decision-making process